Judging victims: why we stigmatize survivors, and how they reclaim respect - Dunn, Jennifer L. (Social problems, social constructions, 2010)
Vocabularies of victimization: sympathy, agency, and identity -- Survivor movements then and now -- The anti-rape movement and blameworthy victims -- The battered women's movement and blameless victims -- "Backlash" and pathetic victims -- Survivors of priest abuse and admirable victims -- The vanguard of victimology: survivors, identity work, and cultural change